The Influence of Service Quality and Product Quality On Customer Loyalty Mediated By Customer Satisfaction In Banking Institutions In Sungai Penuh City (BISNIS, 2025)
This study aims to determine whether service quality and product quality influence customer loyalty, either directly or when mediated by customer satisfaction. A quantitative approach was employed in this research, with primary data collected through an online questionnaire using Google Forms. The population of the study consists of banking customers in Sungai Penuh City, with a sample size of 101 respondents. The data were analyzed using Structural Equation Modeling (SEM) with the SmartPLS 3.2.9 application. The findings reveal that service quality and product quality do not have a direct effect on customer loyalty, and service quality also does not have a direct effect on customer satisfaction. However, product quality has a direct effect on customer satisfaction, and customer satisfaction, in turn, has a direct effect on customer loyalty. Furthermore, customer satisfaction does not mediate the relationship between service quality and customer loyalty, but it does mediate the relationship between product quality and customer loyalty.